Fundamental of Entrepreneurship ENT300 Putih Kelabu Laundry / Jessica Anak James Nyelang... [et al.] - James Nyelang, Jessica; Robert, Rachel Ruran; Mawki, Nur Iffah Amalina; Victor, Nor Aziera Binti; Ahmad Helmy, Nor Hairuni (2014)
Putih Kelabu Enterprise is a partnership company aimed to provide the customers with laundry service. There are five members of this company partnership which consist of the General Manager, Administrative Manager, Operational Manger, Marketing Manager and Financial Manager. The major objective of our company is to cater customers demand for laundry services within Kota Samarahan. Our society nowadays is very concerned about their cleanliness and they want to keep themselves comfortable all the time. One of the best ways to achieve their goal is by sending their clothes to the laundry. We can help them with giving them good services of laundry.